2017
DOI: 10.2147/nds.s136756
|View full text |Cite
|
Sign up to set email alerts
|

Increased eating control and energy levels associated with consumption of bitter orange (<em>p</em>-synephrine) extract: a randomized placebo-controlled study

Abstract: Using a placebo-controlled double-blinded 30-day protocol, 40 overweight adults were asked to consume a chocolate-flavored chew 15-30 min before their two largest meals of the day. The chews contained either a placebo or an "active" product (100 mg of a bitter orange extract, standardized to 51.5 mg p-synephrine). Subjects completed a 13-item Weight Control Support Scale (WCSS) containing eating control, energy level, and palatability subscales daily throughout the study. All 40 subjects completed the study. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
8
0
2
Order By: Relevance
“…Ma, Bavadekar, Schaneberg, Khan, and Feller () concluded that p ‐synephrine acts as an antagonist rather than an agonist with respect to human α‐2a and α‐2c adrenergic receptors. The actions of p ‐synephrine are thought to be mediated at least in part by β‐3 adrenoreceptor activation leading to increased metabolic rate, lipolysis, and reduced food intake (Carpene et al, ; Stohs & Preuss, ; Kaats, Mrivichin, & Stohs, ). Thus, our data support receptor binding studies that would indicate a lack of cardiovascular effects due to poor adrenergic receptor binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma, Bavadekar, Schaneberg, Khan, and Feller () concluded that p ‐synephrine acts as an antagonist rather than an agonist with respect to human α‐2a and α‐2c adrenergic receptors. The actions of p ‐synephrine are thought to be mediated at least in part by β‐3 adrenoreceptor activation leading to increased metabolic rate, lipolysis, and reduced food intake (Carpene et al, ; Stohs & Preuss, ; Kaats, Mrivichin, & Stohs, ). Thus, our data support receptor binding studies that would indicate a lack of cardiovascular effects due to poor adrenergic receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…Kaats et al () administered chocolate‐flavored chews containing 50 mg p ‐synephrine in the form of Advantra Z® (100 mg daily) or placebo 15–30 min before the two largest meals of the day for 15 or 30 days and reported no changes in HR or BP, and no adverse effects were reported. Jung et al () examined a pre‐workout dietary supplement with and without 20 mg of p ‐synephrine and reported no significant changes in HR, BP, and ECG within 30 min of consumption.…”
Section: Discussionmentioning
confidence: 99%
“…No changes in heart rate or blood pressure were noted, and no adverse effects were reported for either the p ‐synephrine‐treated group (103 mg p ‐synephrine per day) or the placebo control group. Statistically significant increases in energy and appetite/eating control were reported with respect to the p ‐synephrine chew as compared with the placebo control chew (Kaats and Stohs, ). This study again demonstrated the absence of cardiovascular effects when consuming up to 103 mg of p ‐synephrine per day.…”
Section: More Recent Human Studiesmentioning
confidence: 99%
“…11 As such, subjects consumed 103 mg p-synephrine or placebo daily. No caffeine was given to the participants, although a majority consumed caffeine on a daily basis.…”
mentioning
confidence: 99%
“…Various effects on lipid metabolism, 10,24,25,57 metabolic rate, 52,58 sport performance, 4 and energy production 11 have been demonstrated at these doses, as well as higher doses of p-synephrine that do not produce cardiovascular effects. 4,10,11,24,25,52,57,58 Therefore, adequate blood levels are achieved to produce these effects without cardiovascular effects. The question remains whether cardiovascular effects can be attained at doses of p-synephrine >100 mg. To date, doses of up to 100 mg p-synephrine per day for 60 days have been shown to be without adverse effects.…”
mentioning
confidence: 99%